Respuesta :

b1 = 2
b2 = (b1)^2 + 1 = 2^2 + 1 = 5
b3 = (b2)^2 + 1 = 5^2 + 1 = 26

b4 = (b3)^2 + 1 = 26^2 + 1 = 676+1=677
So you start off with the given information:
[tex]b_{1}[/tex] = 2
[tex]b_{n}[/tex] = ([tex]b_{n-1}[/tex])² + 1

Since you're looking for the 4th term, that would mean that you are looking for [tex]b_{4}[/tex].
Since you know that we are looking for when n = 4, you can start with what we started off with, which is n = 1, to get to where n = 4.
When n = 1, b = 2,
when n = 2, b = 3,
when n = 3, b = 4,
when n = 4, b = 5.

So the fourth term, when n = 4, is 5.